The LIM/Homeodomain Protein Islet1 Recruits Janus Tyrosine Kinases and Signal Transducer and Activator of Transcription 3 and Stimulates Their Activities - Hao, Aijun (The American Society for Cell Biology, 2005)
Islet1 (Isl1) belongs to the LIM homeodomain transcription factor family. Its roles in differentiation of motor neurons and organogenesis of pancreas and heart have been revealed. However, less is known about its regulatory mechanism and the target genes. In this study, we identified interactions between Isl1 and Janus tyrosine kinase (JAK), as well as signal transducer and activator of transcription (Stat)3, but not Stat1 and Stat5, in mammalian cells. We found that Isl1 not only forms a complex with Jak1 and Stat3 but also triggers the tyrosine phosphorylation of Jak1 and its kinase activity, thereby elevating the tyrosine phosphorylation, DNA binding activity, and target gene expression of Stat3. In vivo, the tyrosine-phosphorylated Stat3 was colocalized with Isl1 in the nucleus of the mouse motor neurons in spinal cord after nerve injury. Correspondingly, electroporation of Isl1 and Stat3 into the neural tube of chick embryos resulted in the activation of a reporter gene expression controlled by a Stat3 regulatory sequence, and cotransfection of Isl1 and Stat3 promoted the proliferation of the mouse motor neuron cells. Our data suggest a novel role of Isl1 as an adaptor for Jak1 and Stat3 and reveal a possible functional link between LIM homeodomain transcription factors and the Jak-Stat pathway.